Selection of the Best Solvent Extract for Antimicrobial Activity Obtained from Marine Mollusca Shells - Thamizharasan , R.; Ravichandran, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Marine organisms are a rich source of structurally novel and biologically active metabolites. So far, many chemically unique compounds of marine origin with different biologically activity have been isolated and a number of them are under investigation and/or are being developed as new pharmaceuticals. Screening of secondary metabolites from Mollusca shell is a common approach to identify compounds of biomedical importance. The aim of the present study is to assessment of antimicrobial activity of different extracts from ten different (Anadara antiquata, Anadara rhombea, Chicoreus virgineus, Donax cuneatus, Mactra violacea, Pugilina cochlidium, Donax scortum, Turritella acutangula, Trachycardium asciaticum and Tonna dolium) Mollusca s shell. The shell powders were immersed separately in ethanol, acetone, methanol and cold steeped for overnight at -18°C. The antimicrobial effects of different (Ethanol, acetone and methanol) extracts were tested against Escherichia coli and Candida albicans strains. The extract obtained from ethanol showed a higher degree of inhibition to the both microbes. Maximum zone of inhibition was exhibited P. cochlidium against E. coli (7.00mm) and C. albicans (5.40mm) by the ethanol extract as compared to other extracts. On the basis of antimicrobial activity of different extracts, ethanol extract is used for further subsequent antimicrobial activities.